1990
DOI: 10.1139/o90-130
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that mammalian ribonucleotide reductase is a nuclear membrane associated glycoprotein

Abstract: Epitope-specific antibodies to the M1 and M2 subunits of mammalian ribonucleotide reductase were prepared using peptides predicted to have a high antigenic index. Western blotting demonstrated that the anti-M1 antibody was specific for the 89-kilodalton M1 subunit (and its degradation fragments) and the anti-M2 antibody specifically recognized the 45-kilodalton M2 subunit. Both antibodies inhibited the CDP-reductase activity of the holoenzyme. Using these antibodies, both the M1 and M2 subunits were shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…In this study, RRM1 was detected to be located near the nucleus in SB cells and GS cells, suggesting that RRM1 may play a role in nuclear membrane. In another study, it demonstrates that RRM1 localizes to the nuclear membrane in the rat liver cell, which is consistent with our results (Sikorska et al 1990). However, in other reports, different cell types including non-small-cell lung cancer (NSCLC) cell lines (Zheng et al 2007) and in human lung fibroblasts cells (Engström and Rozell 1988), RRM1 is expressed in the nuclear and cytoplasmic regions, respectively, suggesting that localization of RRM1 depends on cell type and cellular state.…”
Section: Rrm1 Expression Analysis and Subcellular Localization In Sb Cellssupporting
confidence: 92%
“…In this study, RRM1 was detected to be located near the nucleus in SB cells and GS cells, suggesting that RRM1 may play a role in nuclear membrane. In another study, it demonstrates that RRM1 localizes to the nuclear membrane in the rat liver cell, which is consistent with our results (Sikorska et al 1990). However, in other reports, different cell types including non-small-cell lung cancer (NSCLC) cell lines (Zheng et al 2007) and in human lung fibroblasts cells (Engström and Rozell 1988), RRM1 is expressed in the nuclear and cytoplasmic regions, respectively, suggesting that localization of RRM1 depends on cell type and cellular state.…”
Section: Rrm1 Expression Analysis and Subcellular Localization In Sb Cellssupporting
confidence: 92%
“…Immunocytochemical studies showed that the R1 and R2 subunits of the mammalian RNR enzyme are both localized in the cytoplasm (11) and in some cell types appear to be concentrated near the nuclear region (28). The R2 of the herpes simplex virus type 1 RNR enzyme is concentrated in discrete cytoplasmic foci close to the nucleus, whereas R1 exhibits a more diffuse cytoplasmic localization (4).…”
mentioning
confidence: 99%
“…Although RNR activity has been reported to be present in the outer nuclear membrane, most RNR activity (75%) is present in the cytosol. Furthermore, the changes in the activity in the two fractions are similar during the DNA synthesis phase [37]. To determine the effect of OA on the induction of RNR activity, rats were subjected to two-thirds PH, at which time, in some animals, a 300-mg tablet of OA was implanted i.p.…”
Section: Resultsmentioning
confidence: 99%